The Effect Of Audit Quality, Audit Opinion And Company Size On Audit Report Lag In Listed Mining Sector Companies On The Indonesia Stock Exchange - Januar, Wahyu Wiguna; Gowon, Muhammad; Erwati, Misni (Faculty of Economics and Business Universitas Jambi, 2023)
The purpose of this study is to determine the effect of audit quality, audit opinion, and company size on audit report lag. This study focuses on mining sector companies listed on the Indonesia Stock Exchange (IDX) during the observation period. The sampling technique used is purposive sampling, with selected companies that meet specific criteria related to audit data availability. The data analysis method applied in this study is multiple linear regression. The results of this study show that audit quality and company size have a significant effect on audit report lag, while audit opinion does not have a significant influence. These findings suggest that larger companies tend to have shorter audit report lags, possibly due to better audit preparedness, and that higher audit quality can facilitate a more efficient audit process. The implication of this study is that companies need to improve their internal control systems and audit readiness, especially those with smaller operational scales, to avoid delays in financial reporting. Regulators and auditors are encouraged to consider company characteristics and audit quality when designing audit planning and oversight procedures. Future research could expand the analysis by including variables such as auditor workload, financial distress, or the use of audit technology, and by applying the model across different industry sectors for comparative insights.